KETERAMPILAN GURU MENGADAKAN VARIASI STIMULUS DALAM PEMBELAJARAN BAHASA INDONESIA KELAS V MI NURUL YAQIN SURABAYA - Maraqonitatillah, Maraqonitatillah; Ixfina, Ficky Dewi; Syamsudin, Syamsudin (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2024)
This research investigates the form of stimulus given by teachers to students in learning Indonesian in Class V MI Nurul Yaqin Surabaya. The method in this research uses a descriptive qualitative approach with data collection in the form of interviews, observations and documentation. The findings show that even though teachers have implemented a variety of learning methods and provided motivational support to students, there are still deficiencies in learning interactivity. Research also highlights the role of evaluating learning outcomes, administering punishments and rewards in influencing student motivation. Stimulation results include perceptual responses, emotions, and changes in student behavior. Internal and external factors, such as low interest in learning and a learning environment that is not conducive, become obstacles in providing effective stimulus. Special attention is needed from teachers to correct these deficiencies and create a supportive learning environment for students. In this way, learning Indonesian at MI Nurul Yaqin Surabaya can be more effective and meaningful for student development